2018
DOI: 10.3390/biom8030066
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Oral Inflammations on Cardiac Functions and Atrial Fibrillation

Abstract: Inflammation may be a risk factor for atrial fibrillation (AF). Oral infections frequently lead to chronic inflammation, such as gingivitis, periodontitis, and endodontic lesions. In this narrative review, we consider five basic pathogenic mechanisms that involve oral infections and inflammations in the pathogenesis of AF: (1) low level bacteremia by which oral bacteria enter the blood stream at inflamed sites of the oral cavity and invade the heart; (2) Systemic inflammation induced by inflammatory mediators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 113 publications
1
21
0
2
Order By: Relevance
“…Studies have established that periodontal status and systemic diseases have an effect on each other [1]. The most studied interactions are those between periodontal disease (PD) and cardiovascular conditions [2], rheumatoid arthritis [3][4][5] and diabetes [6][7][8], but relationships between PD and hypertension [8], osteoporosis [9], psoriasis [10,11] pulmonary diseases [12], pregnancy and perinatal complications [13][14][15] have also been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have established that periodontal status and systemic diseases have an effect on each other [1]. The most studied interactions are those between periodontal disease (PD) and cardiovascular conditions [2], rheumatoid arthritis [3][4][5] and diabetes [6][7][8], but relationships between PD and hypertension [8], osteoporosis [9], psoriasis [10,11] pulmonary diseases [12], pregnancy and perinatal complications [13][14][15] have also been shown.…”
Section: Introductionmentioning
confidence: 99%
“…The specific contributions of oral microbiota in human physiopathology has not been explored yet, although different studies report how the composition of oral microbiota has a role in oral and systemic diseases (Santarelli et al, 2015; Sampaio-Maia et al, 2016; Aarabi et al, 2018; Cardoso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, whereas a predominance of Neisseria indicates healthy periodontal conditions, an abundance of Veillonella signi es poor periodontal conditions (53). As mentioned earlier, pathological oral conditions have a deleterious effect on cardiac function, either directly or indirectly through the ANS (11,12), and accumulating evidence indicates that cardiac dysfunction is correlated with insomnia when the ANS is impaired (7-9). Our results regarding oral microbiomes at the genus level are consistent with those observed at the phylum level, because Veillonella and Streptococcus belong to the phylum Firmicutes (54) and Neisseria belongs to the phylum Proteobacteria (55).…”
Section: Discussionmentioning
confidence: 99%
“…Oral microbiota represent one of the most predominant microbial populations in the human body (35,36). Since accumulating evidence indicates that oral microbiota play an important role in health (37)(38)(39), several studies have investigated relationships between oral microbiomes and diseases, especially heart disease (11)(12)(13)(14). A recent report revealed that the diversity and abundance of oral bacteria differ signi cantly in healthy controls and chronic insomnia patients at multiple taxonomic levels (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation